1999
DOI: 10.1536/jhj.40.155
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Morphologic Features of Hypertrophic Cardiomyopathy in Elderly Patients 85 Years or Older.

Abstract: We studied the distinctive morphology of the left ventricle (LV) and attempted to relate advanced age and hypertension to this characteristic feature in elderly patients with hypertrophic cardiomyopathy (HC). Fourteen elderly patients > or = 85 years old (mean age 90 +/- 5 years) with HC were compared with 45 young patients < or = 40 years (mean age 34 +/- 4 years) with this disease. More mild hypertension in the elderly (10/14, 71%) than in the young (0%), and more syncope in the young (10/45, 22%) than in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Whether this decrease was due to a pressure difference or to other non-mechanical factors remains unknown. Aging may be a non-mechanical factor, because basal septal hypertrophy is enhanced, especially in elderly hypertensive patients (13,14). Cardiac angiotensin II is linked to the formation of pressure-overload hypertrophy (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this decrease was due to a pressure difference or to other non-mechanical factors remains unknown. Aging may be a non-mechanical factor, because basal septal hypertrophy is enhanced, especially in elderly hypertensive patients (13,14). Cardiac angiotensin II is linked to the formation of pressure-overload hypertrophy (21).…”
Section: Discussionmentioning
confidence: 99%
“…After 2 or 4 weeks, the hearts were dissected and the LVs were separated into four parts (the base and mid- after blood pressure is controlled (12). Studies have confirmed this prominence of the basal septal hypertrophy in hypertensives, and especially in elderly hypertensives (13,14). These observations suggest that myocardial hypertrophy as a response to pressure overload may develop differently at individual regions of the left ventricle (LV).…”
mentioning
confidence: 85%
“…In one study, the concentric pattern of hypertrophy was found to be more common in elderly patients with HCM, compared with younger subjects in whom asymmetrical hypertrophy was more prevalent 39 . However, other echocardiographic studies do not support these observations 40 . With both the symmetrical and asymmetrical forms of HCM, right ventricular involvement has been reported in 17.6% of cases 27 …”
Section: Macroscopic Phenotypementioning
confidence: 96%
“…Key features that distinguish HCM from hypertensive heart disease are the asymmetric distribution of the hypertrophy and left ventricular outflow tract (LVOT) obstruction. 6,15 Management options in symptomatic patients with hypertrophic obstructive cardiomyopathy (HOCM) are β-blockers, non-dihydropyridine calcium channel blockers, and disopyramide, alone or in combination. Hypertension is frequent as a comorbid condition in these types of patients, and many antihypertensive drugs are relatively contraindicated in HOCM because of the risk of decreased cardiac output, such as diuretics and vasodilators.…”
Section: A B Cmentioning
confidence: 99%